The legal regulation of supplementary mortgage insurance - a comparative study - Professor Ghani Rissan Jader, (The college of law and political science journal, 2023)
Supplementary insurance in the mortgage is one of the penalties resulting from the mortgagor’s breach of his commitment to the guarantee.(A legal penalty that entails compensating the decrease in the value of the pledged money due to its defect or loss, which the mortgagor submits as a result of his request from the pledgor creditor to guarantee the latter’s right in full and undiminished and to restore his right to insurance to what it was at the time of the conclusion of the pledge.